Major changes in chromosomal somy, gene expression and gene dosage driven by SbIII in Leishmania braziliensis and Leishmania panamensis (2019)
Leishmania braziliensis and Leishmania panamensis are two species clinically and epidemiologically important, among others because of their relative resistance to first-line drugs (antimonials). The precise mechanism underlying the ability of these species to survive antimony treatment remains unknown. Therefore, elucidating the pathways mediating drug resistance is essential. We herein experimentally selected resistance to trivalent antimony (SbIII) in the reference strains of L. braziliensis (MHOM/BR75/M2904) and L. panamensis (MHOM/COL/81L13) and compared whole genome and transcriptome alterations in the culture promastigote stage. The results allowed us to identify differences in somy, copy number variations in some genes related to antimony resistance and large-scale copy number variations (deletions and duplications) in chromosomes with no somy changes. We found mainly in L. braziliensis, a direct relation between the chromosomal/local copy number variation and the gene expression. We identified differentially expressed genes in the resistant lines that are involved in antimony resistance, virulence, and vital biological processes in parasites. The results of this study may be useful for characterizing the genetic mechanisms of these Leishmania species under antimonial pressure, and for clarifying why the parasites are resistant to first-line drug treatments. © 2019, The Author(s).